Pectin-Based Nanomaterials: Synthesis, Toxicity and Applications: A Review - Kaur, Mandeep; Wadhwa, Aditya; Kumar, Vineet (Asian Journal of Chemistry, 2021)
Nanomaterials of biological origin are very useful for drug delivery applications. The stability, biodegradability and biocompatibility of pectin nanomaterials in the human body make them an effective drug carrier. This review focus on different aspect of synthesis, drug encapsulation, drug release and safety of pectin-based nanomaterials. The nanomaterials can be used for the delivery of different hydrophilic and hydrophobic drugs to various organs. The release kinetics of drug loaded pectin-based nanoparticles can be studied in vitro as well as in vivo. The pectin-based nanomaterials have good pharmaco-kinetics and can ensure controlled drug delivery. However, the toxicity of pectin-based nanomaterials to human body needs to be evaluated carefully before industrial scale application.